2012
DOI: 10.1042/cbi20120282
|View full text |Cite
|
Sign up to set email alerts
|

TNFα enhances TLR3‐dependent effects on MMP‐9 expression in human mesangial cells

Abstract: The role of MMPs (matrix metalloproteinases) in kidney diseases has been widely accepted, where they can regulate inflammatory response because of their effects on both recruitment and survival of inflammatory cells. TNFα (tumour necrosis factor α) has also been implicated in the pathogenesis of inflammatory kidney diseases, including forms of glomerulonephritis associated with viral diseases. Previously, we established the functional linkage between viral receptors of the innate immune system, the TLRs (Toll-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…It has been indicated that MMPs, particularly MMP-2 and MMP-9, have a key role in podocyte injury (22). Previous studies have also demonstrated that ADR-induced inhibition of podocyte migration and cell injury may be associated with the downregulation of MMP-2 and MMP-9 at the mRNA and protein level (22,23), which was consistent with the results of the present study. Furthermore, the present study indicated that AST increased the expression of MMP-2 and MMP-9 compared with that in the podocyte injury group.…”
Section: Discussionsupporting
confidence: 82%
“…It has been indicated that MMPs, particularly MMP-2 and MMP-9, have a key role in podocyte injury (22). Previous studies have also demonstrated that ADR-induced inhibition of podocyte migration and cell injury may be associated with the downregulation of MMP-2 and MMP-9 at the mRNA and protein level (22,23), which was consistent with the results of the present study. Furthermore, the present study indicated that AST increased the expression of MMP-2 and MMP-9 compared with that in the podocyte injury group.…”
Section: Discussionsupporting
confidence: 82%
“…One possible mechanism of TLR3 involved in the pathogenesis of CKD including lupus nephritis and chronic inflammatory renal disease may be due to its role in triggering the glomerular mesangial cells to produce cytokines and chemokines, factors that can aggravate autoimmune tissue injury [39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…[37] Many studies have shown that MMP9 promotes inflammatory cell aggregation and infiltration, and its high expression in connective tissue diseases often causes joint destruction by degrading the extracellular matrix of the cartilage and bone. [38] Chen et al showed that TGFB1 is highly expressed in the remission phase of GA and contributes to the growth and differentiation of fibroblasts for tissue repair. [39] SIRT1 is significantly deacetylated and involved in physiological processes, including cell cycle regulation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%